The doubly base-stabilized diborane(4) (HB(μ-hpp))2 (hpp = 1,3,4,6,7,8-hexahydro-2H-pyrimido[1,2-a]pyrimidinate): synthesis by catalytic dehydrogenation and reactions with S8 and disulfides - Schulenberg, Nikola; Ciobanu, Oxana; Kaifer, Elisabeth; Wadepohl, Hubert; Himmel, Hans-Jörg (European journal of inorganic chemistry, 2010)
In this work we report on new experiments on the catalytic dehydrogenation of [H2B(μ-hpp)]2 leading to the doubly base-stabilized diborane(4) [HB(μ-hpp)]2 featuring two hpp bridges (hpp = 1,3,4,6,7,8-hexahydro-2H-pyrimido[1,2-a]pyrimidinate) under mild conditions. Several dehydrogenation (pre)catalysts were tested. The best one turned out to be Ru3(CO)12, allowing quantitative dehydrogenation already at 60 °C. Subsequently we subjected [HB(μ-hpp)]2 to reactions with S8 and disulfides (Ph2S2 and Bn2S2, Bn = benzyl). Reaction with S8 leads to oxidative insertion of one sulfur atom into the B-B bond and formation of [HB(μ-hpp)]2(μ-S). In the case of disulfides, substitution reactions leading to the doubly base-stabilized diborane(4) species [RSB(μ-hpp)]2 and HB(μ-hpp)2BSR (R = Ph or Bn) compete with sulfuration again leading to [HB(μ-hpp)]2(μ-S).
Im Titel erscheinen die Bezeichnungen "HB(μ-hpp)" und "1,2-a" in eckigen Klammern
Beim Ausdruck [HB(μ-hpp)]2 erscheint die Ziffer 2 tiefgestellt
Beim Ausdruck S8 erscheint die Ziffer 8 tiefgestellt
Gesehen am 04.07.2023